The Calcium-Sensing Receptor and Integrins in Cellular Differentiation and Migration - Tharmalingam, Sujeenthar; Hampson, David R. (Frontiers in Physiology, 2016)
The calcium-sensing receptor (CaSR) is a widely expressed homodimeric G-protein coupled receptor structurally related to the metabotropic glutamate receptors and GPRC6A. In addition to its well characterized role in maintaining calcium homeostasis and regulating parathyroid hormone release, evidence has accumulated linking the CaSR with cellular differentiation and migration, brain development, stem cell engraftment, wound healing, and tumor growth and metastasis. Elevated expression of the CaSR in aggressive metastatic tumors has been suggested as a potential novel prognostic marker for predicting metastasis, especially to bone tissue where extracellular calcium levels may be sufficiently high to activate the receptor. Recent work has provided evidence supporting a model whereby CaSR-mediated activation of integrins operates as a mechanism underlying cellular migration. Integrins are single transmembrane spanning heterodimeric adhesion receptors that mediate cell migration by binding to extracellular matrix proteins. The CaSR has been shown to form signaling complexes with the integrins to facilitate both the movement and differentiation of cells such as neurons during normal brain development, and of tumor cells under pathological circumstances. Thus, CaSR/integrin complexes may function as a universal cell migration or homing complex. Manipulation of this complex may be of potential interest for treating metastatic cancers, and for developmental disorders pertaining to aberrant neuronal migration.